Loss of p53 triggers WNT-dependent systemic inflammation to drive breast cancer metastasis - Wellenstein, Max D.; Coffelt, Seth B.; Duits, Danique E. M.; van Miltenburg, Martine H.; Slagter, Maarten; de Rink, Iris; Henneman, Linda; Kas, Sjors M.; Prekovic, Stefan; Hau, Cheei-Sing; Vrijland, Kim; Drenth, Anne Paulien; et al. (Nature (London), 2019)
Cancer-associated systemic inflammation is strongly linked to poor disease outcome in patients with cancer 1 , 2 . For most human epithelial tumour types, high systemic neutrophil-to-lymphocyte ratios are associated with poor overall survival 3 , and experimental studies have demonstrated a causal relationship between neutrophils and metastasis 4 , 5 . However, the cancer-cell-intrinsic mechanisms that dictate the substantial heterogeneity in systemic neutrophilic inflammation between tumour-bearing hosts are largely unresolved. Here, using a panel of 16 distinct genetically engineered mouse models for breast cancer, we uncover a role for cancer-cell-intrinsic p53 as a key regulator of pro-metastatic neutrophils. Mechanistically, loss of p53 in cancer cells induced the secretion of WNT ligands that stimulate tumour-associated macrophages to produce IL-1β, thus driving systemic inflammation. Pharmacological and genetic blockade of WNT secretion in p53-null cancer cells reverses macrophage production of IL-1β and subsequent neutrophilic inflammation, resulting in reduced metastasis formation. Collectively, we demonstrate a mechanistic link between the loss of p53 in cancer cells, secretion of WNT ligands and systemic neutrophilia that potentiates metastatic progression. These insights illustrate the importance of the genetic makeup of breast tumours in dictating pro-metastatic systemic inflammation, and set the stage for personalized immune intervention strategies for patients with cancer. Loss of p53 in mouse models of breast cancer leads to activation of WNT signalling, which promotes metastatic spread by inducing systemic neutrophilic inflammation.